2021
DOI: 10.1155/2021/2087876
|View full text |Cite|
|
Sign up to set email alerts
|

Application and Effectiveness of Big Data and Artificial Intelligence in the Construction of Nursing Sensitivity Quality Indicators

Abstract: In order to explore the quality management efficiency of applying big data and artificial intelligence in nursing quality index, a method of building a nursing management platform integrating nursing indicators and nursing events is proposed. Based on the investigation of the application demand of nursing information system, the method achieves timely data sharing and transmission through WLAN technology and realizes nursing management monitoring, nursing quality index enquiry, and automatic statistical analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Quantitatively identify nursing practices that are most relevant to patient outcomes in an effort to improve patient safety and quality of care [ 1 , 2 ]. The indicator management process includes data collection, quality control, data processing, and analysis, identifying key points of changes in nursing quality, selecting implementation measures, and improving program evaluation [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Quantitatively identify nursing practices that are most relevant to patient outcomes in an effort to improve patient safety and quality of care [ 1 , 2 ]. The indicator management process includes data collection, quality control, data processing, and analysis, identifying key points of changes in nursing quality, selecting implementation measures, and improving program evaluation [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] Para ello se precisan de herramientas informáticas que permitan integrar el considerable volumen de datos que se generan cada minuto en las instituciones sanitarias, en diferentes sistemas de información, para poder organizarlos de forma lógica y mediante minería de procesos y aprendizaje automático generar algoritmos e indicadores para la toma de decisiones, así como generar una interfaz gráfica sencilla que permita facilitar su interpretación y toma de decisiones a los profesionales. [4][5][6][7][8] El objetivo de este estudio es elaborar e implementar un software de gestión y planificación de cuidados.…”
Section: Introductionunclassified
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%